Efektifitas Penggunaan Aplikasi Quizlet Terhadap Penilaian Hasil Belajar Siswa Pada Pelajaran IPA Kelas VII Di SMPN 18 Makassar - Efendi , Zulhan; Nasir; Akram (Almeera Education, 2022)
Research on the Effectiveness of Using the Quizlet Application on Assessment of Student Learning Outcomes in Science Lessons on Substances and Their Changes in Class VII 2 Students at SMP Negeri 18 Makassar in the 2022/2023 Academic Year, a total of 30 students. Aims to determine the effectiveness of student learning outcomes by using the Quizlet application in the Natural Sciences subject matter of substances and their changes. This research is a type of quantitative research using experimental methods and the media used in research, namely the Quizlet application. The sample in the research was class VII 2 students. The instruments in this study provided pre- and post-tests to the sample. Data collection techniques used are observation, tests, and documentation. Data analysis techniques are descriptive statistical analysis and inferential statistical analysis. Comparison of learning outcomes categories, and comparisons of completeness levels has proven an increase in class VII 2 student learning outcomes of SMP Negeri 18 Makassar. It can be seen that student learning outcomes through descriptive statistical analysis before using Quizlet media, the average student score is still below the KKM score and after using media quizlet average student scores increased above the KKM score. The finding that the posttest result value is 84 is greater than the pretest result value which is 62.5. Furthermore, based on the results of inferential statistical analysis using the t test formula, it is known that the tcount obtained is 2.326 with a frequency df = 30-1 = 29, at a significant level = 0.05 or 5%, the ttable is 1.699. So tcount > ttable or H0 is rejected and H1 is accepted. Based on these results it can be concluded that there is a significant increase in student learning outcomes. From the results of this study it can be interpreted that through learning media based on the Quizlet application in learning can have an influence on student learning outcomes in class VII 2 Science class SMP Negeri 18 Makassar and provide a positive response to the learning media.